ANALYSIS OF EX MINING LAND USE AS AGROFORESTRY TOURISM IN CISANTANA VILLAGE - Daisy Radnawati; Desy F Makhmud; Suzana K Putri (Universitas Trisakti, 2023)
Cisantana Village is a village in Kuningan Regency, West Java, which is close to Mount Ciremai. Its natural conditions are pretty beautiful. The village has abundant natural resources, one of which is mountain stone. Illegal mountain stone mining activities have become the livelihood of the surrounding community, which, if not stopped, will damage the environment. The problem of land damage due to unlicensed mining activities is environmental damage. For this reason, this research aims to optimize the open land of former mines into agro-tourism land that focuses on education about agricultural and plantation activities that can attract tourists. Agritourism is expected to help restore the quality of the environment that has been damaged and develop the potential that exists in the location through tourism activities. Agritourism is a form of tourism activity carried out in agricultural areas that presents the natural scenery of agricultural areas and their activities (Arifin, 1992). The stages in this research include preparation, inventory, analysis, synthesis, concept, and design. The process of analyzing functions, sites, landscape buildings, and vegetation analysis is carried out as a basis for determining planning directions. Planning activities, the concepts prepared are poured into schematic designs, consisting of spatial arrangement designs, vegetation, sites, landscape buildings, and other details. The result of this research is to optimize Cisantana Village, which is a former mining area, as a sustainable agro-tourism area.